Implicit Theories of Intelligence and Academic Achievement: A Meta-Analytic Review - Costa, Ana; Faria, Luísa (Frontiers in Psychology, 2018)
The current study intended to model the link between implicit theories of intelligence (ITI) and students' academic achievement, within a meta-analytic review procedure. To assess studies’ effect size, the Pearson’s correlation coefficient (r) was used. The review of 46 studies (94 effect sizes) with 412,022 students presented a low-to-moderate association between the ITI and students’ academic achievement. The results indicated that incremental theorists are more likely to have higher grades in specific subjects (verbal and quantitative) and in overall achievement. The entity beliefs were positively associated with students’ specific verbal and quantitative domains but at a lower magnitude than incremental beliefs. Moreover, the moderator effect analyses results indicated that the link between ITI and students’ achievement was not moderated by gender, but there was a moderate association in student’s middle school grade. Additionally, the ITI assessment based on the most recent versions of Dweck’s scales, the use of specific academic scales instead of general ITI scales, and the use of the original measures rather than adapted versions strongly moderated the link between ITI and achievement. Moreover, students from Eastern continents (Asia and Oceania) reported a positive association between incremental beliefs and achievement, Europe displayed a positive link between entity beliefs and achievement, whereas North America presented negative correlations between entity perspectives and academic achievement. This meta-analysis updates the current evidence supporting the direct link of ITI and students’ academic achievement and acknowledges specific effects that ITI could have in different academic outcomes.